Risk-free decision-making - Lobuts, John F. (Journal of business ethics, 1986)
This paper addresses the topic of “risk-free decision-making”, a term which refers to the fact that people are acting “as if” their decisions are “risk-free”. Various social theories are discussed as possible explanations for the growth of this behavior and specific examples are given. Much of the information was drawn from personal experience, current sociological and psychological literature and news events.